URGENCE OF DATA PROTECTION REGULATION UPDATES FOR CONSUMERS AS USERS OF ONLINE LOAN APPLICATIONS - Emanuel Ristian Handoyo (JURTEKSI (Jurnal Teknologi dan Sistem Informasi), 2023)
Abstract: The rapid growth in the use of online loan applications makes protecting consumer data a crucial issue. Current online loan application data protection regulations need to be updated to ensure consumers' personal data is protected from potential misuse. This study aims to analyze the urgency of updating data protection regulations for users of online loan applications through a normative-juridical approach. The results of the study found that more comprehensive new regulations were needed to keep pace with the rapid development of technology in the financial sector. The findings of this study emphasize the importance of protecting personal data in applications that offer online loan services, especially with the increasing number of cases of breaches of personal data. The results of the study conclude that updating personal data protection regulations is very important to ensure the security and safety of consumer data in applications that offer online loan services.            Keywords: application; online loans; personal data protection; regulation; privacy;  Abstrak: Pesatnya pertumbuhan penggunaan aplikasi pinjaman online membuat perlindungan data konsumen menjadi isu krusial. Regulasi perlindungan data pengajuan pinjaman online saat ini perlu diperbarui untuk memastikan data pribadi konsumen terlindungi dari potensi penyalahgunaan. Penelitian ini bertujuan untuk menganalisis urgensi pembaharuan regulasi perlindungan data bagi pengguna aplikasi pinjaman online melalui pendekatan yuridis-normatif. Hasil penelitian menemukan bahwa diperlukan regulasi baru yang lebih komprehensif untuk mengimbangi pesatnya perkembangan teknologi di sektor keuangan. Temuan penelitian ini menekankan pentingnya perlindungan data pribadi dalam aplikasi yang menawarkan layanan pinjaman online, terlebih dengan semakin banyaknya kasus pelanggaran data pribadi. Hasil penelitian menyimpulkan bahwa pembaharuan regulasi perlindungan data pribadi sangat penting untuk menjamin keamanan dan keselamatan data konsumen di aplikasi yang menawarkan layanan pinjaman online. Kata kunci: aplikasi; perlindungan data pribadi; pinjaman online; privasi; regulasi